1987
DOI: 10.2220/biomedres.8.19
|View full text |Cite
|
Sign up to set email alerts
|

<b>STIMULATORY EFFECT OF VASOACTIVE INTESTINAL PEPTIDE (VIP) ON THE GROWTH AND STEROIDOGENIC CAPACITY OF RAT ADRENAL ZONA </b><b>GLOMERULOSA </b>

Abstract: The effects of a prolonged treatment with vasoactive intestinal peptide (VIP) on the morphology and hormone secretion of the rat adrenal gland were investigated. VIP administration caused a significant hypertrophy of the Zona glomerulosa and its parenchymal cells, coupled with a notable rise in the blood level of aldosterone. Zona fasciculata morphology and the blood concentration of corticosterone were not affected. Plasma potassium concentration, the level of circulating ACTH and plasma renin activity did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1987
1987
2003
2003

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In addition, Gallo-Payet et al (1987) and Bornstein et al (1994) referred to the relevant paracrine mechanisms within the adrenal cortex, and several neuropeptides were identified in the gland (Malendowicz, 1993). Concerning adrenal growth, VIP and neuropeptide Y chronically stimulate the growth of zona glomerulosa and aldosterone secretion (Mazzocchi et al, 1987;Rebuffat et al, 19881, but such an effect was observed only when the architecture of the zona glomerulosa was preserved. The effect from VIP seemed to be mediated by local release of adrenaline (Hinson et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Gallo-Payet et al (1987) and Bornstein et al (1994) referred to the relevant paracrine mechanisms within the adrenal cortex, and several neuropeptides were identified in the gland (Malendowicz, 1993). Concerning adrenal growth, VIP and neuropeptide Y chronically stimulate the growth of zona glomerulosa and aldosterone secretion (Mazzocchi et al, 1987;Rebuffat et al, 19881, but such an effect was observed only when the architecture of the zona glomerulosa was preserved. The effect from VIP seemed to be mediated by local release of adrenaline (Hinson et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies in rats however, suggest that VIP is only effective in stimulating aldosterone secretion in the presence of ACTH (66). Further studies showed that long-term (7-day) administration of VIP to intact rats stimulates the growth and steroidogenic capacity of the zona glomerulosa, with no apparent effect on corticosterone secretion and the zona fasciculata (67).…”
Section: The Innervation Of the Adrenal Cortexmentioning
confidence: 93%
“…Some of the neuropeptides identified in the cortex have been shown to exert specific effects on adrenocortical function: vasoactive intestinal peptide stimulates aldosterone secretion in vitro (Cunningham & Holzwarth, 1988), potentiates the effects of ACTH in vivo (Bloom, Edwards & Jones, 1987a; and also stimu¬ lates growth of the zona glomerulosa (Mazzocchi, Robba, Malendowicz & Nussdorfer, 1987); chronic administration of an analogue of methionine-enkephalin stimulates both inner zone and zona glomeru¬ losa function (Robba, Mazzocchi & Nussdorfer, 1986a,Z>); and neuropeptide Y stimulates aldosterone secretion in vivo and chronically causes growth of the zona glomerulosa (Rebuffat, Malendowicz, Belloni et al 1988). …”
mentioning
confidence: 99%